2005
DOI: 10.1021/es050470z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Calcite Precipitation by Natural Organic Material:  Kinetics, Mechanism, and Thermodynamics

Abstract: The inhibition of calcite precipitation by natural organic material (NOM) in solutions seeded with calcite was investigated using a pH-stat system. Experiments were carried out using three NOMs with different physical/chemical properties. For each of the materials, inhibition was found to be more effective at lower carbonate/calcium ratios and lower pH values. The reduction in the precipitation rate could be explained by a Langmuir adsorption model using a conditional equilibrium constant. By identification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
75
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 42 publications
8
75
0
1
Order By: Relevance
“…Other authors have found similar degrees of inhibition of calcite precipitation by DOC in natural systems Suarez, 1996, 1998;Hoch et al, 2000;Lin et al, 2005), and also by dissolved phosphate (Mucci, 1986;Paquette et al, 1986;Dove and Hochella, 1993) and Mg (Nielsen et al, 2013). Dissolved phosphate and Mg concentrations in our soil were < 0.1 µM, which is below values causing inhibition.…”
Section: The Rate Of Precipitationsupporting
confidence: 79%
See 2 more Smart Citations
“…Other authors have found similar degrees of inhibition of calcite precipitation by DOC in natural systems Suarez, 1996, 1998;Hoch et al, 2000;Lin et al, 2005), and also by dissolved phosphate (Mucci, 1986;Paquette et al, 1986;Dove and Hochella, 1993) and Mg (Nielsen et al, 2013). Dissolved phosphate and Mg concentrations in our soil were < 0.1 µM, which is below values causing inhibition.…”
Section: The Rate Of Precipitationsupporting
confidence: 79%
“…Dissolved phosphate and Mg concentrations in our soil were < 0.1 µM, which is below values causing inhibition. The mechanisms of inhibition by DOC involve adsorption of DOC on nucleation surfaces, and the degree of adsorption and resulting inhibition depend on the nature of the DOC and the solution composition (Inskeep and Bloom, 1986a;Lin et al, 2005). Values of DOC of a few mM are typical of mineral soils under natural or seminatural vegetation, depending on the soil organic matter content, clay content, pH and other factors (Moore, 1997;Buckingham et al, 2008).…”
Section: The Rate Of Precipitationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that operation conditions, NOM, many ions such as Mg 2+ , Ba 2+ , Sr 2+ , Mn 2+ and SO 4 2− affect CaCO 3 growth rate. Especially, NOM interacts strongly with calcium carbonate and acts as an inhibitor to calcium carbonate crystal growth in aquatic systems [23][24][25][26][27]. Hence, as a result of heating the feed and enhancement of CF, the solubility of CaCO 3 goes down with temperature rise, and the HCO 3 − ions present in the RCW undergo the decomposition and a considerable amount of CaCO 3 precipitates on membrane surface, which reduces the surface of water vapourization (pores).…”
Section: Crystal Morphology On Membrane Surfacementioning
confidence: 99%
“…The deposit of calcite crystals on the membrane surface was loosely packed and dispersive, and the color of inner membrane surface became brown. It is suggested that NOM acts as an inhibitor to calcium carbonate precipitation by blocking the active growth sites through adsorption reaction [24]. Otherwise, in the RCW, additional protection from scaling may be attained through the use of a number of proprietary antiscalant additives, such as polymaleic acid, phosphonates and non-ionic detergents.…”
Section: Crystal Morphology On Membrane Surfacementioning
confidence: 99%